1990
DOI: 10.1042/bj2710457
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the reaction kinetics of the hexahaem nitrite reductase of the anaerobic rumen bacterium Wolinella succinogenes

Abstract: The reduction kinetics of both the resting and redox-cycled forms of the nitrite reductase from the anaerobic rumen bacterium Wolinella succinogenes were studied by stopped-flow reaction techniques. Single-turnover reduction of the enzyme by dithionite occurs in two kinetic phases for both forms of the enzyme. When the resting form of the enzyme is subjected to a single-turnover reduction by dithionite, the slower of the two kinetic phases exhibits a hyperbolic dependence of the rate constant on the square roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A variety of kinetic mechanisms were investigated to determine whether they could account for the observed kinetic characteristics exhibited by the reaction of metmyoglobin with hydrogen peroxide. Each mechanism was explored in the time domain by using the Gear variable-step numerical integration method to generate theoretical time courses [25]. The time courses were then fitted to the experimental data by varying the rate constants in the scheme being tested.…”
Section: Treatment Of Kinetic Datamentioning
confidence: 99%
“…A variety of kinetic mechanisms were investigated to determine whether they could account for the observed kinetic characteristics exhibited by the reaction of metmyoglobin with hydrogen peroxide. Each mechanism was explored in the time domain by using the Gear variable-step numerical integration method to generate theoretical time courses [25]. The time courses were then fitted to the experimental data by varying the rate constants in the scheme being tested.…”
Section: Treatment Of Kinetic Datamentioning
confidence: 99%
“…Spectrophotometric measurements were made on a Cary 11 8c spectrophotometer. Rapid reactions were performed in a Gibson-Milnes stopped-flow apparatus (Gibson & Milnes, 1964), equipped with a Tracor Northern TN6500 rapid-scan spectrophotometer (Blackmore et al, 1990). Digitized experimental reaction time courses were converted into ASC II files for analysis on a NEC 386SX PC computer.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction traces were analysed in terms of either singleor double-exponential processes, as appropriate, by using non-linear least-squares fitting programs described previously (Brittain, 1986). Numerical simulations of various model reaction systems were performed by using Gear numerical integration techniques (Gear, 1971;Blackmore et al, 1990), employing previously reported algorithms (Brittain, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, reduction of cytochrome P450 by dithionite is used in routine quantitative determinations of the heme protein. Studies of the kinetics of reduction by dithionite were employed to probe apparent conformational transitions and changes in the ligand sphere of the heme iron in such heme-containing enzymes as bovine heart cytochrome c oxidase ( , ), cytochrome bo from Escherichia coli ( , ), and some other biological electron carriers ( ). For most heme proteins studied it was shown that the mechanism of reduction involves the dithionite anion monomer SO •- 2 as the reducing agent ( ).…”
mentioning
confidence: 99%